Risk Factors for Hospital Readmission Following Noncardiac Surgery: International Cohort Study - Michael H. McGillion, RN, PhD; Flavia K. Borges, MD, PhD; David Conen, MD, MPH; Daniel I. Sessler, MD; Brenda L. Coleman, RN, PhD; Maura Marcucci, MD, MSc; Carley Ouellette, RN, MSc; Marissa Bird, RN, PhD; Carly Whitmore, RN, PhD; Shaunattonie Henry, RN, PhD; Sandra Ofori, MD, MSc; Shirley M. Pettit, RN; et al. (Annals of Surgery Open)
Objective:. To determine timing and risk factors associated with readmission within 30 days of discharge following noncardiac surgery. Background:. Hospital readmission after noncardiac surgery is costly. Data on the drivers of readmission have largely been derived from single-center studies focused on a single surgical procedure with uncertainty regarding generalizability. Methods:. We undertook an international (28 centers, 14 countries) prospective cohort study of a representative sample of adults ≥45 years of age who underwent noncardiac surgery. Risk factors for readmission were assessed using Cox regression (ClinicalTrials.gov, NCT00512109). Results:. Of 36,657 eligible participants, 2744 (7.5%; 95% confidence interval [CI], 7.2–7.8) were readmitted within 30 days of discharge. Rates of readmission were highest in the first 7 days after discharge and declined over the follow-up period. Multivariable analyses demonstrated that 9 baseline characteristics (eg, cancer treatment in past 6 months; adjusted hazard ratio [HR], 1.44; 95% CI, 1.30–1.59), 5 baseline laboratory and physical measures (eg, estimated glomerular filtration rate or on dialysis; HR, 1.47; 95% CI, 1.24–1.75), 7 surgery types (eg, general surgery; HR, 1.86; 95% CI, 1.61–2.16), 5 index hospitalization events (eg, stroke; HR, 2.21; 95% CI, 1.24–3.94), and 3 other factors (eg, discharge to nursing home; HR, 1.61; 95% CI, 1.33–1.95) were associated with readmission. Conclusions:. Readmission following noncardiac surgery is common (1 in 13 patients). We identified perioperative risk factors associated with 30-day readmission that can help frontline clinicians identify which patients are at the highest risk of readmission and target them for preventive measures.